CAMK2A supported tumor initiating cells of lung adenocarcinoma by upregulating SOX2 through EZH2 phosphorylation - Wang, Si-Qi (Cell Death Dis, 2020)
Tumor initiating cells (TIC) of lung cancer are mainly induced by stress-related plasticity. Calcium/Calmodulin dependent protein kinase II alpha (CAMK2A) is a key calcium signaling molecule activated by exogenous and endogenous stimuli with effects on multiple cell functions but little is known about its role on TIC. In human lung adenocarcinomas (AD), CAMK2A was aberrantly activated in a proportion of cases and was an independent risk factor predicting shorter survivals. Functionally, CAMK2A enhanced TIC phenotypes in vitro and in vivo. CAMK2A regulated SOX2 expression by reducing H3K27me3 and EZH2 occupancy at SOX2 regulatory regions, leading to its epigenetic de-repression with functional consequences. Further, CAMK2A caused kinase-dependent phosphorylation of EZH2 at T487 with suppression of EZH2 activity. Together, the data demonstrated the CAMK2A-EZH2-SOX2 axis on TIC regulation. This study provided phenotypic and mechanistic evidence for the TIC supportive role of CAMK2A, implicating a novel predictive and therapeutic target for lung cancer.